SPECIFIC CHARACTERISTICS OF GREEN MARKETING PRACTICES IN TEXTILE ENTERPRISES (International journal of artificial intelligence, 2026)
The growing importance of environmental sustainability has accelerated the adoption of green marketing strategies in textile industry enterprises worldwide. The textile sector is considered one of the most environmentally sensitive industries due to excessive water consumption, chemical pollution, greenhouse gas emissions, and waste generation. Under these conditions, green marketing has become an important strategic tool for ensuring environmental responsibility, improving enterprise competitiveness, and meeting international sustainability standards. This study examines the specific aspects of using green marketing instruments in textile enterprises and analyzes their role in sustainable industrial development. The paper explores the theoretical foundations of green marketing, sustainable fashion, and environmentally responsible supply chain management based on contemporary scientific literature. Particular attention is devoted to the integration of ecological principles into all stages of the textile value chain, including raw material selection, production processes, packaging, logistics, and product distribution.